A Comprehensive Review on Design of Autonomous Robotic Boat for Rescue Applications. (22nd June 2021) - Jain, Vanita; Saini, Dharmender; Gupta, Monu; Joshi, Neeraj; Mishra, Anubhav; Bansal, Vishakha; Jude Hemanth, D.
Abstract : New technologies are advancing and emerging day by day to improve the safety of humans by making use of various autonomous technologies. The continuous utilization of autonomous vehicles/systems in search and rescue (SAR) operations is a challenging research area particularly for marine-based activities. A comprehensive systematic literature review (SLR) providing an overview of improvisations that have been done in the field of autonomous technologies for search and rescue operation over the last five years has been compiled in this paper. A methodology for using autonomous vehicles in water for SAR operations has been incorporated and demonstrated. The focus of this study is to look at the various techniques and address different challenges faced for human beings' safety during rescue operation. The comparison of results achieved for various technologies and algorithms is highlighted in this paper. This literature survey proves to be a good source of information for fellow researchers to precisely analyze the study results.